Optimization of Government Management in the Implementation of Smart Governance to Enhance the Efficiency of Public Services in Bekasi City - Dwi Saputro, Sudarmo; Muda, Satria Kadir; Triambodo, Firlannang; Gumilang, Inggil; Amelia, Neneng Widya (Dinasti Research, 2025)
This study aims to analyze the optimization of government management in the implementation of smart governance to enhance the efficiency of public services in Bekasi City. As the public demand for fast, transparent, and accountable services continues to increase, local governments are required to adopt technology- and data-based governance systems. This research employs a qualitative approach using semi-structured interviews, observations, and document studies involving government officials and public service users. The findings indicate that the implementation of smart governance in Bekasi City has shown significant progress through the development of the Public Service Mall (MPP), online complaint channels, and the digitalization of administrative services. However, the efficiency of public services remains hindered by weak inter-agency coordination, limited information system integration, and the low digital competency of government personnel. Optimal implementation of smart governance requires strengthening government management aspects, particularly in data-driven strategic planning, cross-unit integration, and human resource capacity building. Thus, the success of the transformation toward smart governance in Bekasi City depends on the synergy between technological innovation, effective governance, and public participation in delivering efficient and sustainable services.